Konsep Pendidikan Modern dalam Perspektif Al-Qur’an - Suparman, Heru (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2018)
Abstract. The research findings state that the views or reviews of the Koran regarding Modern Education are basically in accordance with Islamic teachings, especially the Koran which is the source of Islamic law. Other interesting findings in research on Modern education include the Qur'anic criticism of modern education, the goals of Islamic education, and the person in charge of Islamic education. From some of these characteristics, formulated with verses of the Koran and interpretations as an argument, that the concept of modern education is in harmony with the teachings of Islam in regulating the order of human life on this earth, especially in the context of education. The author can conclude that Modern Education is ways of learning in accordance with the demands of the present era, to be prepared by students in their time.